Diffusion Coefficients in Electrolyte Mixtures─Influence of the Solute Characteristics - Hewa Kankanamge, Chathura Jayan Kankanamge; Klein, Tobias; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2025)
Fick diffusion coefficients D11 of binary electrolyte mixtures consisting of seven different solutes dissolved in either acetonitrile (ACN) or diethyl carbonate (DEC) are presented. The solutes were selected with respect to a systematic variation of their characteristics such as size, mass, polarity, and charge delocalization. D11 was determined by dynamic light scattering (DLS) and molecular dynamics (MD) simulations at temperatures up to 398 K and at a solute amount fraction of 0.05. The results contribute to an extension of the existing database for D11 in binary electrolyte mixtures and allow its investigation as a function of the solute characteristics. With the help of MD simulations, the coordination or solvation number, which represents the solvation of solute ions by solvent molecules present in the first solvation shell, could be accessed and used to investigate the influence of the fluid structure on D11. Here, for ACN as a solvent, a larger D11 for the solute [Na][NTf2] in comparison to that for [Li][NTf2] could be attributed to a less defined and more fragile solvation shell surrounding the larger [Na]+ cation.
CRIS-Team Scopus Importer:2025-02-21